The use of Jigsaw II technique in Malay grammar learning - Hasnida Ahmad; Muhammad Zuhair Zainal (Universitas Pendidikan Indonesia, 2023)
The Jigsaw II technique has been found to be effective in teaching and learning grammar based on cooperative learning. Therefore, this study was conducted to examine the effect of the use of the Jigsaw II technique on Form Four students’ attitudes and achievement in Malay grammar learning. Sixty-two students from two boarding schools in Kubang Pasu district, Kedah, Malaysia, were selected to participate in the study. They were divided into a treatment group and a control group. Thirty-one students of the treatment group used the Jigsaw II technique, while thirty-one students of the control group used the Gallery Walk technique. Both groups were given pre-test and post-test. Pre-attitude and post-attitude questionnaires were given to the treatment group only. Data was collected and analysed quantitatively using paired sample t-test, independent sample t-test, and simple linear regression test. The results showed a significant difference in achievement and attitudes for the treatment group in learning Malay grammar after using the Jigsaw II technique. The analysis also showed that the student’s attitude also influenced their achievement in learning Malay grammar based on the Jigsaw II technique. In conclusion, language teachers should choose and diversify cooperative learning techniques, such as the Jigsaw II technique, as this technique can also influence students’ achievement and attitudes in grammar learning.